As implicações da formação inicial no processo de iniciação à docência dos egressos do curso de Letras do Centro de Estudos Superiores de Tefé, estado do Amazonas - Bezerra, Rita de Cássia Eutrópio Mendonça (2022)
Teaching knowledge is the result of a historical process through which teachers transform the knowledge they have had access to throughout their training and professional activities into learning that is mobilized in the professional practice. Initial training has a fundamental role in teacher training. The beginning of teaching for graduates of the Language course is similar to that of other graduates at a time when there is a transition from student to teacher, in which they will have to face the dilemmas and difficulties characteristic of the early career. Thus, initiation to teaching is characterized as a period of intense learning, which can traumatize and awaken in teachers the necessity to survive the challenges of the profession. This impact on school reality leads teachers to (re)signify their work practice to improve their actions in the classroom. Also during this period, teachers will establish interactions with other agents in the school community (supervisors, guidance counselors, directors, teachers) and outside it (family members, professional colleagues from other schools and academic training spaces), building some important logic that may become definitive for their teaching actions. The research was carried out between 2017 and 2018 with five beginning teachers, graduates in the Portuguese Language Degree Course at the Center for Higher Studies in Tefé city at the State University of Amazonas. The general objective was to understand, through training narratives, the implications of initial training in the teaching initiation process of graduates of the Languages course at the Center for Higher Studies in Tefé (AM). The results indicate: a) built learning, from the perspective of graduates of the Portuguese Language course, in initial training and in other training processes and how they were mobilized (or not) at the beginning of teaching; b) difficulties at the beginning of the teaching, how they face them and if initial training subsidies are identified for coping with them; c) practices developed by the beginners, which they consider successful, and which were built from the experiences lived in the initial formation and in other formative experiences.